Rhodesian land deeds in modern Zimbabwe - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
For much of the last century the Fengu people living near Bulawayo in Zimbabwe, have held title deeds to their land. In this report the chief of the Fengu explains how the title deeds have helped them, and how his people are responding to the current land redistribution programme in Zimbabwe.